The incarnatorial dynamismn according to Theodore of Mopsuestia’s catechetical homilies - Uríbarri Bilbao SJ, Gabino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The Christology of the Council of Chalcedon is widely recognised as a «Descending Christology», whose weak points were clearly perceived and described in modern theologies. An «Ascending Christology» was preferred by post-conciliar theologies. This Christology assumes the «anthropological revolution» of modernity, rediscovers the «historical Jesus», examines the historical dimension of the relationship between humanity and divinity in Jesus Christ, and regains for Christology a reflection about the Holy Spirit and the eschatological event of the Resurrection. Some of these questions were already foreseen by the Antiochean School, mainly by one of its greatest theologians, Theodore of Mopsuestia (350-428). Focusing on his catechetical homilies, which are his best preserved work, an exposition and appraisal of his Christological proposals are offered in this paper. Although expressed in somewhat abstract, unfamiliar terms and philosophical categories, his suggestions emerge as a possible light and inspiration for modern theologians.
Keywords: christology; incarnation; Theodore of Mopsuestia; Church Fathers